Layout optimization methods and tools: A systematic literature review - Chemim, Lucas Stelle (2021)
Purpose: This article aims to show the methods used to optimize layout and tools that have been applied since 2010 in the most diverse production environments.Theoretical Reference: Due to the intense competitiveness and uncertainties in the current market, improving processes and increasing production efficiency by managing the layout of a facility can be one of the methods to benefit organizations. In this context, knowledge of the main tools and methods is essential in defining the conduct of studies.Design/methodology/approach: Research was carried out through a systematic literature review. The databases used were Science Direct and Portal Capes. Using keywords, a defined scope and the relevance of the theme, international articles were selected for reading and discussion.Findings: Through the review, it was possible to select 51 articles which were relevant to the topic. Due to the complexity of the layout management study, it was found that increasingly more algorithms, mathematical and computational models are being used to solve these NP-hardness problems.Research, Practical & Social implications: adjusting to new methods and ways of solving problems laying out facilities, although scenarios can be extremely varied, they can improve business results by making the process more efficient.Originality/value: The article compiles and briefly explains the methods found to optimize the layout, which is of great importance considering the knowledge that these models spread on production management practices.Keywords: Layout optimization. Algorithm. Method. Facility layout planning.